CARE/CARING: ELEMENTS AND DIMENSIONS FROM A PERSPECTIVEOF PERSONS ADMITTED TO A UNIVERSITY HOSPITAL - Lillian Daisy Gonçalves Wolff; Luciana Schleder Gonçalves; Simone Beatriz Yede (Universidade Federal do Paraná, 1998)
This descriptive and exploratory study unveils the inpatients' perspective and dimensions of care/caring in an university hospital. Data were collected through a semistructured interview, with seven questions used to identify the one-cared and the care giver feelings and attributes, as well as the conditions for be cared, the results and what people do while is being cared. The interviewers found that caring is not only about technical procedures and scientific knowledge in practice. It demands that the caregiver must have clinical and interpersonal competence. Clinical competence is responsibility, the search of knowing, the attention, dedication, and competence to attend the client's needs of proper diagnoses, care, comfort and treatment, by the clients expectation. Interpersonal competence is the psycho-social ability needed in caring relationship. The interpersonal abilities pointed by the clients in this study are: vocation, having sense of humanity, express affection, establish human relationship grounded in sincerity, good humor, patience, sensitivity and courtesy. Caring means an union between two human beings, built through sharing their life experiences, the revealing of their selves, resulting in mutual developing and learning and in bringing out the humanity inside each one of them. Caring happens in a social-economical, geographic and cultural context, where both caregiver and being-cared are influenced. The clients recognize the environmental influence and the being cared and the caregiver's role, as well as the essential attributes for those who care. In addition, they show themselves sensitive to the caregiver's emotions during the caring process. The nurses need to be aware towards the care/caring elements elucidation, analyzing them in each context and historical moment, because they show direction, method and technology to caring implementation. That's why it is of major importance that the nursing researchers become very articulated with practice, bringing together all actors of caring: nursing professionals, client, family and community.